1987
DOI: 10.1007/bf01313902
|View full text |Cite
|
Sign up to set email alerts
|

Restricted viral antibody specificity in many ferrets infected with the ferret Aleutian disease parvovirus

Abstract: The majority of ferrets infected with a ferret strain of Aleutian disease virus (ADV) produce antibody only to a detergent-sensitive common determinant on the two closely related virion proteins. Ferrets with high antibody titers and mink infected with this virus also produce antibody to one or more virion immunogenic determinants unaffected by detergent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A number of uncharacterized ADV isolates also exist (11,39,45,49,51), and animals other than mink may be reservoirs of ADV infection (10,36,44,50). For example, seroprevalence in ferrets to ADV can be as high as 42% (49,65,66), but although ADV-ferret causes mild lesions in ferrets, it is not pathogenic for mink (66). A number of other mustelids, including weasels, fishers, marten, striped skunks, and otters, can also be infected with ADV, but studies are even more limited than in ferrets (44,50,73).…”
mentioning
confidence: 99%
“…A number of uncharacterized ADV isolates also exist (11,39,45,49,51), and animals other than mink may be reservoirs of ADV infection (10,36,44,50). For example, seroprevalence in ferrets to ADV can be as high as 42% (49,65,66), but although ADV-ferret causes mild lesions in ferrets, it is not pathogenic for mink (66). A number of other mustelids, including weasels, fishers, marten, striped skunks, and otters, can also be infected with ADV, but studies are even more limited than in ferrets (44,50,73).…”
mentioning
confidence: 99%
“…Antiviral antibodies commonly reach titers in excess of 1/10 6 and can constitute over one-half of the gamma globulins (1)(2)(3)43). Gamma globulins can comprise up to 50% of the total serum proteins (1)(2)(3), and in some instances, mink develop a gamma globulin pattern that exhibits evidence of restricted heterogeneity or monoclonality (2,8,42).…”
mentioning
confidence: 99%
“…previously reported experiments (10,12,13), which used 6 and 10% separating polyacrylamide gels, failed to show unequivocal visual evidence of a viral protein of this size. However, sera from uninfected mink gave a moderately high level of background staining on bands in this size range.…”
mentioning
confidence: 74%
“…Analysis of the antibody response to ADV in mink and ferrets by immunoprecipitation and Western immunoblotting has shown that essentially all infected animals with progressive or nonprogressive disease develop antibody to 86,000and 78,000-dalton (Da) virion proteins (VP-1 and VP-2, respectively) and to a 71,000-Da nonvirion protein (NS-1) (6,13). Some infected ferrets develop antibody only to detergent-sensitive determinants on VP-1 and VP-2 (12). A 143,000-Da protein demonstrable only by Western blotting appears to be a dimer of NS-1.…”
mentioning
confidence: 99%